Restoring Carboxylates on Highly Modified Alginates Improves Gelation, Tissue Retention and Systemic Capture. (15th January 2022) - Moody, CT; Brown, AE; Massaro, NP; Patel, AS; Agarwalla, PA; Simpson, AM; Brown, AC; Zheng, H; Pierce, JG; Brudno, Y
Abstract: Alginate hydrogels are gaining traction for use in drug delivery, regenerative medicine, and as tissue engineered scaffolds due to their physiological gelation conditions, high tissue biocompatibility, and wide chemical versatility. Traditionally, alginate is decorated at the carboxyl group to carry drug payloads, peptides, or proteins. While low degrees of substitution do not cause noticeable mechanical changes, high degrees of substitution can cause significant losses to alginate properties including complete loss of calcium cross-linking. While most modifications used to decorate alginate deplete the carboxyl groups, we propose that alginate modifications that replenish the carboxyl groups could overcome the loss in gel integrity and mechanics. In this report, we demonstrate that restoring carboxyl groups during functionalization maintains calcium cross-links as well as hydrogel shear-thinning and self-healing properties. In addition, we demonstrate that alginate hydrogels modified to a high degree with azide modifications that restore the carboxyl groups have improved tissue retention at intramuscular injection sites and capture blood-circulating cyclooctynes better than alginate hydrogels modified with azide modifications that deplete the carboxyl groups. Taken together, alginate modifications that restore carboxyl groups could significantly improve alginate hydrogel mechanics for clinical applications. Statement of significance: Chemical modification of hydrogels provides a powerful tool to regulate cellular adhesion, immune response, and biocompatibility with local tissues. Alginate, due to its biocompatibility and easy chemical modification, is being explored for tissue engineering and drug delivery. Unfortunately, modifying alginate to a high degree of substitution consumes carboxyl group, which are necessary for ionic gelation, leading to poor hydrogel crosslinking. We introduce alginate modifications that restore the alginate's carboxyl groups. We demonstrate that modifications that reintroduce carboxyl groups restore gelation and improve gel mechanics and tissue retention. In addition to contributing to a basic science understanding of hydrogel properties, we anticipate our approach will be useful to create tissue engineered scaffolds and drug delivery platforms. Graphical abstract: Image, graphical abstract